Criminal Responsibility for Child Abuse as a Perpetrator of a Criminal Act is Linked to Maqashid Syari'ah: Pertanggungjawaban Pidana Perundungan Anak Sebagai Pelaku Tindak Pidana Dihubungkan Dengan Maqashid Syari’ah - Hidayat, Sarip; Akhmaddhian, Suwari; Adhyaksa, Gios; Gumilar , Doni Cakra (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
Protection children are very important to fulfill to child face to face with law Good as perpetrator follow criminal, as a victim of an act criminal nor as witness follow criminal. Needed renewal law about protection child Because follow criminal bullying often occurs in the environment kids, fine as perpetrator as well as victims. Constitution Number 35 of 2014, which is change from Constitution Number 23 of 2002 concerning Child protection . Method used in Study This can categorized as as study juridical-normative. Study juridical normative referring to the regulations legislation, decisions courts, and practice law in Society results study accountability criminal for child must see to the age limit child Because in Constitution Number 11 of 2012 concerning System Justice Child Crime. only arrange child the from 12 years old until with 18 years, correlation principle protection with Maqasid Sharia is form harmony between law positive with draft law Islam namely, guarding religion, guarding soul, guard resourceful, guarded offspring and care treasure. Very deep enforcement law Good nature preventive nor repressive for child as perpetrator follow criminal order not to happen repetition deed criminal.